READY TO WEAR CLOTHING WITH BATIK MOTIFS INSPIRED BY CISADANE LENGGANG DANCE - Zanira, Zahra Alfina (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2023)
The work on the final project batik motif with the source of the idea of Dance Lenggang Cisadane for clothing Ready to Wear. The purpose of this final project that is, creating Batik motifs dance Lenggang Cisadane with the main motive in the dance movement that rests on the four elements of culture in dance Lenggang Cisadane. The method used in the process of creating this work is Gustami method which is divided into three methods, namely starting from the exploration stage, by making direct observations at the location of the dance studio and digging for data through interviewing. The second stage is the design, starting with alternative designs to be selected as batik motifs applied to ready-to-wear clothing. Starting from the process of pattern, shading, batik, coloring, melorod, sewing to finishing. The results in the creation of this work in the form of four ready to wear clothing. His attributes are softie, beauty, agility and cheerfulness. The creation of fashion works that raise the motif of Dance Lenggang Cisadane can be known more widely in the general public, especially the younger generation who are less aware of traditional dance culture.